(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Air pollution remains a critical environmental and public health challenge in Shanghai, driven by seasonal variations in criteria pollutants such as PM2.5, PM10, SO2, NO2, O3, and CO. This study examines monthly and long-term trends in air quality using data from 2014 to 2024, highlighting the influence of anthropogenic emissions, and regulatory measures. The results indicate that particulate matter (PM2.5 and PM10) and NO2 peak during winter due to increased coal-based heating, industrial activities, and atmospheric stagnation, while O3 concentrations rise in summer due to enhanced photochemical reactions. SO2 and CO levels remain relatively stable throughout the year, reflecting the success of emission control policies. The Air Quality Index (AQI) closely aligns with PM concentrations, with the highest pollution levels occurring in winter and the lowest in autumn. Many pollutants, particularly PM2.5 and NO2, exceed World Health Organization (WHO) guidelines, posing significant health risks. The findings underscore the urgent need for season-specific mitigation strategies, including stricter winter emission controls and summer ozone management policies. Enhancing air quality requires comprehensive approaches such as transitioning to clean energy, improving industrial emissions standards, and expanding public transportation infrastructure.